Preferences of Low-Cost Passengers, Low Cost Airlines and Airport Management on Low Cost Terminal (LCT) Facilities Development Model - Sabar, Rohafiz; Anuar, Nur Khairiel; Abdullah, Rohani (International Journal of Supply Chain Management, 2018)
The purpose of the Paper is to examine the provision of passenger facilities in Low Cost Terminals (LCTs) after reviewing a selection of LCT models at airports in the Asia Pacific, European and United States regions, and supported by an in-depth survey of low cost passenger, low cost airline and airport management preferences related to operations at the Low Cost Terminal, Kuala Lumpur International Airport. The forecasting of passenger profiles is important so that the airport can establish an adequate terminal design which may be able to cope with an acceptable level of service to the passengers while, at the same time, the terminal is able to generate sufficient commercial revenues from the LCC customers. Taking account of the LCC profiles, the airport needs to pay attention by ensuring their preferences for facilities and level of service should be included in the terminal design. The decision by airport management for the provision of specific terminal facilities (TFs) may be dependent on budget restrictions, cost of investment, land availability and the preferences of the major customers, that is, in the case of LCTs, the low-cost carriers (LCCs). Consequently, most (but not all) LCT designs are based on the concept of a basic terminal layout with limited terminal facilities in order to reduce both construction and operating costs, a shorter construction time, acceptable service standards and minimum aircraft turnaround time. However, there are contradictions. For example, passenger expectations of level of service and terminal facilities do not always coincide with those of airline and airport management. Furthermore, a consequent low level of aeronautical revenue drives the requirement to maximise commercial revenues. The paper will conclude by suggesting guidelines for LCT development that will seek to optimise the relative aspirations of all parties concerned.